2000
DOI: 10.1108/eum0000000005383
|View full text |Cite
|
Sign up to set email alerts
|

The DBA: what is it for?

Abstract: The 1990s have seen the emergence and development of professional doctorates in the UK and, in particular, the Doctor of Business Administration (DBA). This article identifies the rationales offered for DBA programmes and their intended learning outcomes. Research findings are based on programme documentation produced by the 16 universities offering the DBAs in 1999. Analysis of these documents shows that these programmes have been designed to provide research‐based career development for experienced and senio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…The DBA is one of a number of professional doctorates which developed in response to the perceived need to provide an alternative to the traditional PhD to serve careers outside of academia . Indeed, Bareham et al's (2000) analysis suggests that DBAs have been designed to provide research-based career development for senior professionals in management. Of note then, most practitioners have already established their careers before commencing on a DBA and it is suggested that they hold 'intrinsic personal' motivations for study (Scott et al, 2004).…”
Section: The Dbamentioning
confidence: 99%
“…The DBA is one of a number of professional doctorates which developed in response to the perceived need to provide an alternative to the traditional PhD to serve careers outside of academia . Indeed, Bareham et al's (2000) analysis suggests that DBAs have been designed to provide research-based career development for senior professionals in management. Of note then, most practitioners have already established their careers before commencing on a DBA and it is suggested that they hold 'intrinsic personal' motivations for study (Scott et al, 2004).…”
Section: The Dbamentioning
confidence: 99%
“…Banerjee and Morley (2013) observe that DBAs are offered by some 37% of UK universities. The DBA was one of a number of professional doctorates which developed in response to the perceived need to provide an alternative to the traditional PhD and to serve careers outside of academia (Bareham, Bourner, & Stevens, 2000). Indeed, Bareham et al's (2000) analysis suggests that DBAs have been designed to provide researchbased career development for senior professionals in management.…”
Section: The Dba: Program Description and Backroundmentioning
confidence: 99%
“…The DBA was one of a number of professional doctorates which developed in response to the perceived need to provide an alternative to the traditional PhD and to serve careers outside of academia (Bareham, Bourner, & Stevens, 2000). Indeed, Bareham et al's (2000) analysis suggests that DBAs have been designed to provide researchbased career development for senior professionals in management. Typically, students will possess significant managerial experience as well as holding a relevant Masters qualification.…”
Section: The Dba: Program Description and Backroundmentioning
confidence: 99%
See 2 more Smart Citations